Innovation Capability Mediation: Market Orientation and Consumer Orientation on the Success of MSME Bag Businesses in Ciampea District, Bogor - Alicia Nurfitriani Ramadhanti; Erny Amriani Asmin; Yulianingsih Yulianingsih (JURNAL ECONOMINA, 2026)
This study aims to analyze the effect of market orientation and customer orientation on business success by considering the role of innovation capability as an intervening variable among bag SMEs in Ciampea District, Bogor. This research employed a quantitative approach using descriptive and associative methods with path analysis. The research sample consisted of 100 bag SME owners in Ciampea District, Bogor, selected using a purposive sampling technique. Data were collected through questionnaires and analyzed using IBM SPSS Statistics version 26. The results indicate that market orientation and customer orientation have a positive and significant effect on innovation capability and business success. In addition, innovation capability also has a positive and significant effect on business success. Furthermore, the findings reveal that innovation capability is able to mediate the relationship between market orientation and customer orientation on business success. These findings imply that strengthening market orientation and customer orientation, supported by innovation capability, can enhance business success among bag SMEs in Ciampea District, Bogor.